PENGARUH PERSEPSI PROFESI DAN KESADARAN ETIS TERHADAP KOMITMEN PROFESI AKUNTAN (STUDI PADA KANTOR AKUNTAN PUBLIK KOTA PALEMBANG) - Hartania Indraswati; Aris Munandar (Universitas Indo Global Mandiri)
This thesis discusses about the influence of professional perception and ethical awareness to the commitment of the public accountant profession study conducted at the public accounting firm that exist in the city of palembang.. The population in this study are the auditors who work in the Public Accounting Firm in Palembang City Of the total population of 40 auditors, the researchers took a sample of 40 respondents based on the total number of KAP (10) with 3 to 5 questionnaires for each KAP . Sampling method in this research is determined by the method of selecting probability samples, which is simple random sampling. Data collection techniques in this study using a questionnaire (kuisoner). Data were collected by questionnaire. Data analysis technique used in this research is multiple regression analysis, F test, coefficient of determination test, T test, and Test of classical assumption. Hypothesis testing is used to determine the important influence between professional perception and ethical awareness of professional commitment. The results of hypothesis testing showed that there is a positive and significant influence between professional perceptions and ethical awareness of the commitment of the public accounting profession.Keywords: Profession Perception, Ethical Awareness, Profession Commitmen